Meta-Analysis of the Effect of Prolonged Use of High Heels on Low Back Pain in Female Sales Employees - Fadhila Firmanurulita; Agus Kristiyanto; Hanung Prasetya (Masters Program in Public Health, 2023)
Background: Low Back Pain is the pain that is felt from the lower back area to the lower buttocks crease area (Gluteal inferior fold). One of the causes of Low Back Pain is a prolonged and excessive use of high heels. This study aims to analyze and estimate the effect of the use of high heels on Low Back Pain in sales promotion girls. Subjects and Method: Meta-analyses were carried out according to the PICO model. Population: female sales promotion employee. Intervention: Wearing High Heels. Comparison: Not using High Heels. Outcome: Low Back Pain. The article search in this study was conducted through databases that included PubMed, Google Schoolar, ScienceDirect. The keywords included: